Adventurous tourism-a potetial realm of world Natural Heritage - National Park Phong Nha - Ke Bang - Nghi, Tran; Phuong, Ta Hoa; Phai, Vu Van; Thanh, Dinh Xuan; Lan, Nguyen Thanh; Thai, Nguyen Dinh; Hong, Nguyen Thi (VNU Journal of Science: Earth and Environmental Sciences; Vol 27 No 2, 2011)
Abstract. World Heritage National Park Phong Nha - Ke Bang has been and is being invested by the government in general and by Quang Binh province in particular to expand into a population with different types of tourism in order to invite domestic and foreign tourists. Since the 60s of 20th century, the Phong Nha - Ke Bang zone has been regarded as a tourism spot that attracts the most number of tourists among the tourism industry of Quang Binh province. However, since then this National Park has only exploited the exterior caves and has not, together with other types of tourism, extended its activities in all national Forest’s territory. Therefore, in this article the authors’s group will begin to explain in details of other potential adventurous tour types of Phong Nha - Ke Bang region in particular and of Quang Binh province in general, these are: to explore the caves in adventurous tours upon limestone mountains with perpendicular cliffs by road 20, cable - riding tours through National Park zone where the cables are put on the highest mountain peaks, adventurous eco-tours inside proteozoic forests famous for a most diversified and abundant ecosystem in South East Asia. These are the potential and valuable types of tour assuring a great charm for a huge number of tourists inside and outside the country.